REGURGITATION AND REFLUX SYNDROME IN CHILDREN OF EARLY AGE - I.N. Zakharova; E.N. Andryukhina (Педиатрическая фармакология, 2010)
One of the clinical manifestations of discernible gastroesophageal reflux (GER) in young children is regurgitation which is caused by gastric contents passing into fauces. Regurgitation may be both physiological and pathological. According to S. R. Orenstein’s data (2001), it may occur at least once a day in half of infants during the first three months, in two thirds of infants under 4 months and only in 5% of infants aged 10–12 months. A percentage of infants may have pathological GER characterised by a constant and prolonged reflux of acid stomach contents into oesophagus and accompanied by developing inflammation with express clinical manifestations. Pathological GER may cause an unexpected death in infants during sleep. The unequivocal conclusion, therefore, is that gastroesophageal reflux should be treated! This article covers the key causes of them as well as tactics for correction and treatment. Key words: regurgitation, vomiting, projectile vomiting, gastroesophageal reflux, oesophagus, stomach, regurgitation, exicosis, oesophagitis. (Pediatric Pharmacology. – 2010; 7(4):106-112)